The effects of two intramuscular sedation protocols on echocardiographic variables in cats following sedation and blood donation. Issue 2 (13th March 2021) - Reader, Rebecca C.; Yang, Vicky K.; Babyak, Jonathan M.; Abelson, Amanda L.
Abstract: Objective: To compare effects of 2 IM sedation protocols, alfaxalone‐butorphanol (AB) versus dexmedetomidine‐butorphanol (DB), on echocardiographic (ECHO) variables in cats following sedation and blood donation. Design: Experimental randomized, blinded crossover study. Setting: University teaching hospital. Animals: Eleven client‐owned healthy cats. Interventions: Cats received a baseline ECHO without sedation prior to their first donation. Cats were sedated intramuscularly with AB (alfaxalone, 2 mg/kg, and butorphanol, 0.2 mg/kg) for 1 donation and DB (dexmedetomidine, 10 μg/kg, and butorphanol 0.2, mg/kg) for another, with a minimum 6 weeks between donations. A post‐sedation, post‐donation ECHO was performed after each blood donation. Measurements and main results: Eight cats completed the study. Compared to baseline, DB combined with blood donation decreased heart rate (−84/min; P  < 0.0001), fractional shortening (−16.5%; P  < 0.0001), ejection fraction (‐21.0%; P  = 0.0002), and cardiac output (−292 mL/min, P  = 0.0001); AB combined with blood donation increased heart rate (+45/min; P  = 0.0003) and decreased left ventricular end diastolic volume (−1.57 mL; P  < 0.0001). Compared to AB, DB decreased heart rate (−129/min; P  < 0.0001) and fractional shortening (−21.6%; P  < 0.0001) and increased left ventricular end‐systolic (+1.14 mL; P  = 0.0004) and diastolic volumes (+1.93 mL; P  < 0.0002). Cats administered DB had a significant increase in regurgitant flow across mitral, aortic, and pulmonic valves following blood donation ( P  < 0.05). One cat administered DB developed spontaneous echo contrast in the left ventricle following donation. Conclusions and clinical relevance: Compared to AB, DB had more pronounced effects on ECHO variables in cats following IM sedation and blood donation. Due to its minimal impact on ECHO variables, AB may be a more desirable sedation protocol in this population of cats.